The long-term treatment of restless legs syndrome/Willis–Ekbom disease: evidence-based guidelines and clinical consensus best practice guidance: a report from the International Restless Legs Syndrome Study Group - Garcia-Borreguero, Diego; Kohnen, Ralf; Silber, Michael H.; Winkelman, John W.; Earley, Christopher J.; Högl, Birgit; Manconi, Mauro; Montplaisir, Jacques; Inoue, Yuichi; Allen, Richard P. (Sleep medicine, 2013)
A Task Force was established by the International Restless Legs Syndrome Study Group (IRLSSG) to develop evidence-based and consensus-based recommendations for the long-term pharmacologic treatment of restless legs syndrome/Willis–Ekbom disease (RLS/WED). The Task Force reviewed the results of all studies of RLS/WED treatments with durations of 6months or longer presented at meetings over the past 2years, posted on Web sites of pharmaceutical companies, or published in peer-reviewed journals, asking the questions, “What is the efficacy of this treatment in patients with RLS/WED?” and “What is the safety of this treatment in patients with RLS/WED?” The Task Force developed guidelines based on their review of 61 papers meeting inclusion criteria, and using a modified evidence-grading scheme. Pregabalin has been established as effective for up to 1year in treating RLS/WED (Level A evidence). Pramipexole, ropinirole, and rotigotine have been established as effective for up to 6months in treating RLS/WED (Level A). The following drugs have been established as probably effective (Level B) in treating RLS/WED for durations ranging from 1 to 5years: gabapentin enacarbil, pramipexole, and ropinirole (1year); levodopa (2years); and rotigotine (5years). Because of associated safety concerns, pergolide and cabergoline should not be used in the treatment of RLS/WED unless the benefits clearly outweigh the risks. Other pharmacologic therapies have insufficient evidence to support their long-term use in treating RLS/WED. The IRLSSG Task Force also developed consensus-based strategies for the prevention and treatment of complications (such as augmentation, loss of efficacy, excessive daytime sleepiness, and impulse control disorders) that may develop with the long-term pharmacologic treatment of RLS/WED. The use of either a dopamine-receptor agonist or α2δ calcium-channel ligand is recommended as the first-line treatment of RLS/WED for most patients, with the choice of agent dependent on the patient’s severity of RLS/WED symptoms, cognitive status, history, and comorbid conditions.